2000
DOI: 10.1023/a:1013009006522
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The estrogenic activities of chemicals for dental and similar use were tested by a reporter gene assay (yeast two-hybrid system) and an estrogen/estrogen receptor (ER-alpha) competition binding assay (fluorescence polarization system). Among the 10 chemicals [bisphenol-A (BPA), bis-2-hydroxypropyl methacrylate (Bis-GMA), triethylene glycol dimethacrylate (TEGDMA), methyl methacrylate (MMA) and 2-hydroxyethyl methacrylate (HEMA), dibutyl phthalate (DBP), n-butyl benzyl phthalate (BBP), n-butyl phthalyl n-butyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…36 In another study, BPA, but neither bis-GMA nor TEGDMA, showed estrogenic activity. 57 Other studies have revealed that only BPA and bis-DMA, but not bis-GMA, interacted with the estrogen receptor. 25 More recently, BPA and bis-DMA were shown to be estrogen agonists, androgen antagonists, and inhibitors of aromatase activity at the receptor level.…”
Section: Estrogenic Activity Of Bpa and Bpa Derivativesmentioning
confidence: 96%
“…36 In another study, BPA, but neither bis-GMA nor TEGDMA, showed estrogenic activity. 57 Other studies have revealed that only BPA and bis-DMA, but not bis-GMA, interacted with the estrogen receptor. 25 More recently, BPA and bis-DMA were shown to be estrogen agonists, androgen antagonists, and inhibitors of aromatase activity at the receptor level.…”
Section: Estrogenic Activity Of Bpa and Bpa Derivativesmentioning
confidence: 96%
“…Although the estrogenicity of BPA has been demonstrated in vitro and in vivo, only a few studies have examined the estrogenicity of BPA derivatives. These studies have primarily been performed in vitro and have found bis-DMA but not bis-GMA (the more common ingredient of most dental resins) to be estrogenic (26, 27). …”
Section: Discussionmentioning
confidence: 99%